Hyperuricemia in obese children and adolescents: the relationship with metabolic syndrome - Li Tang; Masaru Kubota; Ayako Nagai; Kimiyo Mamemoto; Masakuni Tokuda (MDPI AG, 2010)
The prevalence of hyperuricemia in obese children and adolescents and its association with metabolic syndrome are largely unknown. The objective of our study was to characterize hyperuricemia in relation to metabolic syndrome in Japanese children and adolescents with obesity. Between 2005 and 2008, we performed a cross-sectional study of 1,027 obese children and adolescents aged 6-14 years. Based on the reference value of serum uric acid we had established previously, hyperuricemia was defined as one standard deviation over the mean value at each age. The diagnosis of metabolic syndrome was made based on the Japanese criteria for children. A total of 213 children and adolescents (20.7%) was found to have hyperuricemia. The prevalence of hyperuricemia was significantly higher in the male gender and older age group. Sixty-five out of 213 subjects with hyperuricemia (30.5%) had metabolic syndrome, whereas 111 out of 814 subjects without hyperuricemia (13.6%) had metabolic syndrome. The most common abnormal component of metabolic syndrome was triglyceride, followed by diastolic blood pressure, systolic blood pressure, fasting blood glucose, and HDL-cholesterol. Such a tendency was almost identical between the two groups. We concluded that considering the association between hyperuricemia and metabolic syndrome in obese Japanese children and adolescents, the role of hyperuricemia in metabolic syndrome should receive more attention, beginning in early childhood.